Harmonisation of Shari’ah, Common law and Customary Law in Nigeria: Problems and Prospects - Oba, Abdulmumini A (Journal of Malaysian and Comparative Law, 2019)
Law in Nigeria is traceable to three distinct legal traditions namely customary law, Islamic law and the English common law. These laws often differ irreconcilably in substantive law, procedural law, concepts of justice, and worldviews. The colonial administration ensured the ascendancy of the common law in the country but the movement in support of Islamic law has remained very strong. Thus, there exist a lot of tensions within the Nigerian legal system. Various approaches have been suggested to resolve these conflicts. Some have suggested a unification of the three systems of law. Others, towing the colonial policy want the specialist courts administering Islamic and customary laws abolished. The biggest obstacle to unification of laws in Nigeria is that Islam does not permit for Muslims a hybrid law out of Islamic law and any other law. Muslims have argued in favour of a clear separation of Islamic law from common law and for the establishment of a parallel system of courts from the lowest to the highest court to deal with each of the three laws in the country. This parallel system of courts has many challenges and there may still be a case for administering Islamic law by specialists within a unified courts system. Law in Nigeria took a new turn in 1999 with the adoption of Islamic law as the basic law in many States in northern Nigeria. The changes introduced Sharia Penal Codes and Sharia Courts. Non-Muslims are not subject to Islamic law. The major obstacles to these reforms include constitutional limits, Muslim themselves, and non-Muslims both on the national and international fronts. Muslims must therefore show more commitment and dedication to the cause of Islamic law if they want to see full-fledged Islamic law entrenched firmly in the country.